A haptic learner model. (6th February 2006) - Lloyd, Tim; Bull, Susan
This paper describes an adaptive learning environment with an open learner model to promote learner reflection. The learner model can be presented using different techniques: textual and haptic. The paper investigates the potential for haptic learner models in terms of whether users can understand a haptic model, and whether they find it useful. Most liked both versions, but of those with a preference, more found the haptic method of interaction useful. However, some liked the textual version, suggesting the need for a variety of methods of accessing the model to be available in learning environments with an open learner model.